Safety Program for the assembly and disassembly processes of Trópika, habitation module, in the Solar Decathlon 2014 competition - Ortega-Rojas, Adelina; Blanco-Moraga, André (Instituto Tecnológico de Costa Rica, 2014)
This project was made for the participation of Team Tec (Tech Team Costa Rica) in intercollegiate competition, Solar Decathlon Europe (SDE), France 2014. In this competition 20 universities from around the world must design, build and test a housing module that works with solar energy and must be sustainable. The organization of the SDE requires compliance with European safety standards, which have a higher level than the ones in Costa Rica. To meet the level of security that should be, was defined as a general objective to propose a Safety Program for the assembly and disassembly process of the Trópika, habitation module proposed by Tec Team for the competition. In order not only to meet the requirements of the organization, but also to strengthen the safety of team members. Among the main results are the following:  During assembly the members of the team will be exposed to activities that involve risks with extreme level.  Any team member has experience about construction works, which increase the risk of accident or incident.  The knowledge of the team members in construction safety matters is deficient.  SDE organization requires higher level of safety during all the stages of the project but especially during the assembly and disassembly process. In response to the above a Safety Program for the assembly and disassembly of Trópika was developed, incorporating safety aspects that should be followed during these processes, safe work procedures in order to guide the team members in the work was prepared to be conducted. It also contains a training plan and an emergency plan. With this tool Tec Team is benefited mainly to have a guide document to perform the work of more securely way which helps to protect and care for the integrity of the team members.
Proyecto de Graduación (Bachillerato en Ingeniería en Seguridad Laboral e Higiene Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Seguridad Laboral e Higiene Ambiental, 2014.
Keywords: Riesgos; Construcción; Variables; Análisis; Organización; Competencia; Seguridad